2019
DOI: 10.1002/bjs.11298
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide study of appendicitis in children

Abstract: Background: Paediatric surgical care is increasingly being centralized away from low-volume centres, and prehospital delay is considered a risk factor for more complicated appendicitis. The aim of this study was to determine the incidence of paediatric appendicitis in Sweden, and to assess whether distance to the hospital was a risk factor for complicated disease. Methods: A nationwide cohort study of all paediatric appendicitis cases in Sweden, 2001-2014, was undertaken, including incidence of disease in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 26 publications
2
33
0
4
Order By: Relevance
“…Less than 19% of children have a complicated acute appendicitis; hence, the majority of children with uncomplicated AA may be considered for either a non-operative or an operative management [ 112 ].…”
Section: Resultsmentioning
confidence: 99%
“…Less than 19% of children have a complicated acute appendicitis; hence, the majority of children with uncomplicated AA may be considered for either a non-operative or an operative management [ 112 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in this context, increasing travel distance was not associated with adverse outcome in paediatric appendicitis, which may reflect the generally shorter distances to emergency hospitals. 38 A few studies of cryptorchidism, in various healthcare systems and populations, have reported treatment delays for children with worse insurance status or lower average income and education in neighbourhood area of residence. 2 21 This effect seems context specific, as indicated by a Canadian study showing that average deprivation status and income level in area of residence did not associate with treatment delays in paediatric surgery in general.…”
Section: Discussionmentioning
confidence: 99%
“…The risk for developing AA during one’s lifetime is 8.6% for men and 6.7% for women, with the illness most often occurring between the ages of 10 and 30 [ 3 ]. In a study by Omling et al [ 4 ] conducted on a group of 38,939 children, the estimated risk of the appearance of AA in patients under age 18 was 2.5%. In epidemiological studies, geographical variations have been noted in the incidence of the illness over the course of a lifetime, with a frequency of 16% in South Korea, 9% in the USA, and 1.8% in Africa [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%